Rompendo com o lugar de abandono: contradições, dilemas e desafios do acolhimento institucional - Campos, Márcia Cristina (2019)
Thisresearchaims to comprehend and analyzethe essence of the contradictions and paradoxes that permeate theprotective measuresin institutional shelters, withemphasis on the misunderstandings and distortions produced by the agents responsible for its recommendation, determination and execution.This research arisesfrom the concerns present in the everyday practice of the socialworkprofessionals of the Childhood and Youth Court. Such concerns emerge when facing the ethical dilemmas and challenges present in the social reality of children and adolescentsina sheltering situation, who, contrary tolegal prerogatives,are subjected several times to violationsof rightspracticed exactlyby the institutions thatwere supposed to protect them.Thisdocumental qualitative research was based on sheltering case filesources, which have allowed complete access to the overly prolongedinstitutional trajectories that violate the provisory and exceptional nature of the action and,consequently, the fundamental right to both familiar and communitarian life.The investigative path was meantto dive into Luna, Lucas and Alice’s stories. They had their childhood and adolescence crossed bysheltering measuresunfoldeda seriesof violence, violations, and ruptures that have marked their experiences inside of these shelters. Throughout this research study, many important aspects concerning the procedural protocols were revealed, making evident how things are developed in thesemeasures and, above all,how the violationof rights happen even when they are hidden under the apparentconditionof legality. Among the findings, it was found that the lack of social protection that follows the examined families’ history has had a decisive influence on the outcomes of the sheltering measure. It exposes the persistence of the social practice oninsisting onpoverty criminalization and judicialization of social matter, therefore showingexpressions one of its most perverse faceswhen it comes to the childhood and youth institutionalization. It indicates that the expressive advances achieved in the legal grounds are still in need of the permanent individual and collective efforts in its full realization and in its battle against the setback risks, witha view to implementingthe child and adolescentfull protection doctrine